Pembelian Impulsif, Buy Now Pay Later (BNPL), dan Konsumerisme: Perspektif Governmentality dalam Masyarakat Digital - Azzahra, Altarisya Salsabila (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Impulsive purchasing and consumerism in digital society have intensified with the widespread adoption of Buy Now Pay Later (BNPL) services, particularly among Generation Z. While BNPL provides short-term financial flexibility, its imprudent use encourages excessive consumption and heightens the risk of financial distress, especially given Gen Z’s relatively low level of financial literacy. This study examines the interrelationship between BNPL, consumerism, impulsive buying behavior, and financial literacy among Generation Z through the framework of governmentality. The research aims to analyze how BNPL policies and market strategies shape consumer subjectivity, assess the moderating role of financial literacy, explore the dynamics of Fear of Missing Out (FOMO) and social legitimation, and derive policy implications. Using a qualitative literature review of primary and secondary sources, the study finds that BNPL operates as a subtle mechanism of governmentality by normalizing debt through ease of access, aggressive promotion, and digital platform design. Personalization algorithms and behavioral nudges stimulate impulsive buying, reinforced by hedonic motivation, FOMO, social media influence, and limited self-control. Low financial literacy exacerbates impulsive behavior, while mental accounting reduces perceived debt risk. The study highlights the need for stronger financial education, adaptive regulation, and ethical responsibility among BNPL providers.